Aeromonas veronii, a tributyltin (TBT)-degrading bacterium isolated from an estuarine environment, Ria de Aveiro in Portugal - Cruz, A. (2007)
Organotin compounds are used in a variety of industrial processes therefore their subsequent discharge into the environment is widespread. Bacteria play an important role in biogeochemical transformations acting as natural decontamination agents. Therefore, screening for tributyltin (TBT)-resistant and -degrading bacteria is relevant for the selection of isolates with decontamination ability of these polluted areas. With this purpose, 50 strains were isolated from sediment and water from Ria de Aveiro and their tolerance to TBT, up to 3 mM, was evaluated. Generally, occurrence of highly TBT-resistant bacteria was observed, and Gram negative bacteria exhibited more tolerance to TBT than Gram positive bacteria. A memory response was observed when bacteria were progressively exposed to increasingly higher TBT concentrations. One isolate, Aeromonas veronii Av27, highly resistant to TBT (3 mM) uses this compound as carbon source and degrades it to less toxic compounds.